Parallel sensory compensation following independent subterranean colonization by groundwater salamanders ( Eurycea ) - Ruben U. Tovar; Brittany A. Dobbins; Nicholas R. Hartman; Sheena Leelani; Thomas J. Devitt; Dana M. García; Paul M. Gignac; David C. Cannatella; David M. Hillis (Proceedings of the National Academy of Sciences, 2025)
Lineages that have invaded subterranean environments have repeatedly evolved remarkable adaptations to life in darkness. However, observational and experimental studies in additional natural systems are needed to further our understanding of repeated evolution and convergence. In Texas, a radiation of groundwater salamanders (genus Eurycea ), with independent invasions of subterranean karstic environments, offers an opportunity to investigate phenotypic convergence, parallel evolution, and the enhancement and regression of sensory systems. Adaptations to a troglobitic life in this clade include morphological, behavioral, and physiological changes within and among species. Intraspecific and interspecific variation in morphology in response to the selective pressures of life underground allows for detailed examination of physical, behavioral, and physiological changes associated with subterranean adaptation within a comparative phylogenetic framework. We find a correlated change between two sensory systems repeated across multiple subterranean Eurycea lineages: the degeneration of the eye and the expansion of the mechanosensory lateral line. The increase in anterior neuromast organs in subterranean lineages was positively correlated with the expression of pax6 (Paired-box 6), a conserved transcription factor important for vertebrate neurogenesis. Our results show a decreasing trend of PAX6 labeling in the neuromasts of adult surface salamanders ( Eurycea nana ) relative to the maintained labeling in subterranean species ( Eurycea rathbuni ). These lateral line enhancements are correlated with reductions in the development of optic systems in subterranean salamander lineages. Altogether, our findings provide a starting point for future evolutionary developmental investigations examining the genetic underpinnings of adaptive, repeated evolution in a novel system.